Identifikasi Telur Cacing Ascaris lumbricoides Pada Feses Balita Di Wilayah Kerja Puskesmas Ponre - Harma, Andi Harmawati Novriani HS; Ridwan, Asriyani; I Gusti Agung Ayu Satwikha Dewi (Jurnal TLM Blood Smear, 2024)
Infectious diseases still often occur in developing countries, one of which is infection caused by parasites in the form of worms. Soil Transmitted Helminths (STH) are intestinal nematodes which in their life cycle require soil for the maturation process so that there is a change from a non-infective stage to an infective stage. The prevalence of worms in Indonesia is still quite high, between 60-80%, especially in children under five because at that age they move more and interact directly with the environment. This research aims to determine the presence of Ascaris Lumbricoides worm eggs in the feces of toddlers in the Ponre Community Health Center Working Area. The type and design of the research used is observational with a cross sectional design. Stool examinations will start from June to November 2023 on 20 stool samples. Sample analysis was carried out in the Microbiology Laboratory DIII Health Analyst Stikes PHB. Microscopic results of Soil Transmitted Helminths (+) worm eggs from 12 people. The frequency of Soil Transmitted Helminths infections is based on the type of worm eggs with details of Ascaris lumbricoides 12 people.